Complement Receptor 2 Based Immunoassay Measuring Activation of the Complement System at C3-Level in Plasma Samples From Mice and Humans - Halkjær, Lene; Troldborg, Anne; Pedersen, Henrik; Jensen, Lisbeth; Hansen, Annette Gudmann; Hansen, Troels Krarup; Bjerre, Mette; Østergaard, Jakob Appel; Thiel, Steffen (Frontiers in Immunology, 2020)
We aimed at establishing a sensitive and robust assay for estimation of systemic complement activation at complement component C3 level in mouse and human plasma samples. In order to capture the activation products iC3b and C3dg in a specific and physiological relevant manner we utilized a construct consisting of the iC3b/C3dg-binding site of human complement receptor 2 (CR2) attached to an Fc-part of mouse IgG. This construct binds C3dg and iC3b from both mice and humans. We purified the CR2-IgG construct from mouse B myeloma cell line supernatants, J558L-CR2-IgG, by protein G affinity chromatography. The CR2-IgG construct was used for capturing C3 fragments in microtiter wells and an anti-mouse or an anti-human-C3 antibody was used for detection of bound C3 fragments. Initially we tested the specificity of the assays with the use of purified C3 fragments. Further, with the use of the CR2-based assay, we measured an up to three-fold higher signal in activated mouse serum as compared to non-activated mouse serum, whereas activated serum from a C3 knock-out mouse gave no signal. We tested in vivo generated samples from a mouse experiment; complement activation was induced by injecting cobra venom factor or heat aggregated IgG into C57bl6 mice, followed by withdrawal of EDTA blood samples at different time points and measurement of iC3b/C3dg. We observed a clear time-dependent distinction in signals between samples with expected high and low complement activation. Furthermore, with the use of the assay for human C3 fragments, we observed that patients with systemic lupus erythematosus (SLE) (n=144) had significantly higher iC3b/C3dg levels as compared to healthy individuals(n=144) (p<0.0001). We present two functional immunoassays, that are able to measure systemic levels of the C3-activation products iC3b and C3dg in mice and humans. To our knowledge, these are the first assays for complement activation that use a physiological relevant capture construct such as CR2. These assays will be a relevant tool when investigating mouse models and human diseases involving the complement system